Evolution of Developmental Programs for the Midline Structures in Chordates: Insights From Gene Regulation in the Floor Plate and Hypochord Homologues of Ciona Embryos - Oonuma, Kouhei; Yamamoto, Maho; Moritsugu, Naho; Okawa, Nanako; Mukai, Megumi; Sotani, Miku; Tsunemi, Shuto; Sugimoto, Haruka; Nakagome, Eri; Hasegawa, Yuichi; Shimai, Kotaro; Horie, Takeo; et al. (Frontiers in Cell and Developmental Biology, 2021)
In vertebrate embryos, dorsal midline tissues, including the notochord, the prechordal plate, and the floor plate, play important roles in patterning of the central nervous system, somites, and endodermal tissues by producing extracellular signaling molecules, such as Sonic hedgehog (Shh). In Ciona, hedgehog.b, one of the two hedgehog genes, is expressed in the floor plate of the embryonic neural tube, while none of the hedgehog genes are expressed in the notochord. We have identified a cis-regulatory region of hedgehog.b that was sufficient to drive a reporter gene expression in the floor plate. The hedgehog.b cis-regulatory region also drove ectopic expression of the reporter gene in the endodermal strand, suggesting that the floor plate and the endodermal strand share a part of their gene regulatory programs. The endodermal strand occupies the same topographic position of the embryo as does the vertebrate hypochord, which consists of a row of single cells lined up immediately ventral to the notochord. The hypochord shares expression of several genes with the floor plate, including Shh and FoxA, and play a role in dorsal aorta development. Whole-embryo single-cell transcriptome analysis identified a number of genes specifically expressed in both the floor plate and the endodermal strand in Ciona tailbud embryos. A Ciona FoxA orthologue FoxA.a is shown to be a candidate transcriptional activator for the midline gene battery. The present findings suggest an ancient evolutionary origin of a common developmental program for the midline structures in Olfactores.